Comparison of lipid biomarker and gene abundance characterizing the archaeal ammonia-oxidizing community in flooded soils - Bannert, A.; Mueller-Niggemann, C.; Kleineidam, K.; Wissing, L.; Cao, Z.; Schwark, Lorenz; Schloter, M. (Springer, 2011)
In the last years, archaea have been identified as key players in global N cycling, especially in nitrification. Ammonia-oxidizing archaea (AOA) are postulated to belong to the new phylum Thaumarchaeota for which the lipid crenarchaeol should be specific. The ratios between two independent markers for AOA, the ammonia monooxygenase gene and crenarchaeol have been studied in different aerated soils, but so far not in flooded soils. This study investigated ammonia-oxidizing archaea in four paddy soils and a tidal wetland. Ratios were significantly higher in the paddy soils compared to the tidal wetland and in general higher as in upland soils, leading to the assumption that archaeal ammonia oxidizers different from crenarchaeol-containing Thaumarchaeota may play an important role in paddy soils. © 2011 Springer-Verlag.